Controlled Atmosphere Storage and Sorbitol Dipping Minimize Chilling Injuries in ‘Palmer’ Mangoes - da Silva, Maryelle Barros [UNESP]; Pedrosa, Vanessa Maria Dantas [UNESP]; Izidoro, Maiqui [UNESP]; Balbuena, Tiago Santana [UNESP]; Sanches, Alex Guimarães [UNESP]; de Almeida Teixeira, Gustavo Henrique [UNESP] (MDPI, 2024)
Our previous studies have shown that ‘Palmer’ mangoes immersed in solutions containing 2.5% sorbitol and stored under a controlled atmosphere (CA) at 8 °C for 30 days had fewer symptoms of a chilling injury. However, there is no information regarding the effectiveness of sorbitol treatment in other atmospheres and/or in combination with lower temperatures. Thus, the objective of this study was to assess the impact of dipping ‘Palmer’ mangoes in 0.1% and 2.5% (w/v) sorbitol solutions and storing the fruit under a CA without atmosphere modification (21 kPa O2 + 0.03 kPa CO2) at 8 °C/95% relative humidity (RH) or with 5 kPa O2 + 5 kPa CO2 at 4 °C/95% RH for 28 days. The fruits were evaluated periodically for chilling injuries, quality, and oxidative metabolism. A chilling injury (CI) was correlated with increased fresh weight loss (FWL) and changes in the color of the epicarp (Lpeel, h°peel, and Cpeel) and mesocarp (L*pulp). Lipid peroxidation (LPpulp and LPpeel) and the hydrogen peroxide content (H2O2peel and H2O2pulp) were associated with the development of a CI, particularly after being transferred to ambient. The treatment with 2.5% sorbitol was more effective in minimizing the chilling injury symptoms and did not compromise the fruit quality, especially when it was stored at 4 °C in association with a CA containing 5 kPa O2 + 5 kPa CO2. This treatment reduced lipid peroxidation and increased the activities of the superoxide dismutase (SOD) and ascorbate peroxidase (APX) enzymes in the epicarp and mesocarp, providing greater cold tolerance. The use of 2.5% sorbitol has been identified as the most efficacious approach for mitigating the adverse impacts of chilling injuries, preserving the fruit quality, and enhancing oxidative metabolism, even at lower temperatures. Thus, this treatment represents a viable alternative for managing chilling injuries in mangoes.
Keywords: APX; Mangifera indicaL; oxidative metabolism; polyols; SOD